Case Report: PTEN Mutation Induced by anti-PD-1 Therapy in Stage IV Lung Adenocarcinoma - Teng, Junjie; Zhou, Kai; Lv, Dongxiao; Wu, Changshun; Feng, Hong (Frontiers in Pharmacology, 2022)
Lung cancer is the most common solid tumor in the worldwide. Targeted therapy and immunotherapy are important treatment options in advanced non-small cell lung cancer (NSCLC). The association of PTEN mutation and tumor immunotherapy is less established for patients with NSCLC. We present the case of an Asian woman diagnosed with stage IV lung adenocarcinoma harboring an ERBB2 mutation. She received Nivolumab treatment when her disease progresses after previous chemotherapy and Afatinib treatment. However, the patient did not response to Nivolumab. PTEN mutation was detected by next-generation sequencing (NGS) after treatment with Nivolumab. PTEN, a secondary mutation, may be served as a biomarker of resistance to anti-PD-1 immunotherapy in lung adenocarcinoma. The relationship between PTEN mutation and immunotherapy is complex and needs further study.